"There is no one right family": Young Children's Discussions About Family Diversity. (2nd October 2022) - Kim, So Jung; Hachey, Alyse C.
Abstract: By sharing episodes of young children's authentic conversations about diverse families, the authors provide an expanded vision of early literacy education as a medium for social justice, equality, and transformation.